BERMAIN SEBAGAI INTERVENSI UNTUK MENINGKATKAN KOMPETENSI SOSIAL ANAK - Muchtar, Hendi Suhendraya; Razak, Alifah Indalika Mulyadi (Jurnal Pendidikan Usia Dini, 2018)
This study aims to examine the play stimulation model to improve children's social competence. The study involved 100 children in the kindergarten age group. The types of play in this study are divided into four games patterns, namely the solitary independent play, parallel play, associative play, and cooperative play. Each play pattern is tested with four dimensions of social competence, which consist of self-concept, ability to manage emotions, prosocial and social-academic behavior. The results of this study indicate that more than 50% of the four dimensions of social competence are effectively stimulated through cooperative play patterns. Cooperative play patterns are effective for stimulating self-concept dimensions (10 of 15 behaviors), emotional management abilities (9 of 18 behaviors), social academics (7 of 15 behaviors), and prosocial behavior (17 of 23 behaviors). The pattern of associative play effectively stimulates the dimensions of self-concept (3 of 15 behaviors), emotional management skills (7 of 18 behaviors), prosocial behavior (4 of 23 behaviors), and social academics (3 of 15 behaviors). The effective parallel play and solitary independent play patterns of each play only stimulate 1 social competence behavior. Keywords: cooperative play, associative play, parralel play, solitary independent play, social Competencies Penelitian ini bertujuan untuk menguji model stimulasi permainan untuk meningkatkan kompetensi sosial anak. Penelitian ini melibatkan 100 anak pada kelompok usia taman kanak-kanak. Jenis permainan pada penelitian ini terbagi ke dalam empat pola permainan, yaitu solitary independent play, parralel play, associative play, dan cooperative play. Setiap pola permainan diujikan dengan empat dimensi kompetensi sosial, yang terdiri dari konsep diri, kemampuan mengelola emosi, perilaku prososial dan sosial-akademik. Hasil penelitian ini menunjukkan bahwa lebih dari 50% empat dimensi kompetensi sosial efektif distimulasi melalui pola permainan cooperative play. Pola permainan cooperative play efektif untuk menstimulasi dimensi konsep diri (10 dari 15 perilaku), kemampan mengelola emosi (9 dari 18 perilaku), sosial akademik (7 dari 15 perilaku), dan perilaku prososial (17 dari 23 perilaku). Pola permainan associative play efektif menstimulasi dimensi konsep diri (3 dari 15 perilaku), kemampuan mengelola emosi (7dari 18 perilaku), perilaku prososial (4 dari 23 perilaku), dan sosial akademik (3 dari 15 perilaku). Pola permainan parralel play dan solitary independent play masing-masing efektif hanya menstimulasi 1 perilaku kompetensi social. Kata Kunci: Anak Usia Dini, Bermain Kooperatif, Bermain Asosiatif, Bermain paralel, Bermain soliter, Kompetensi sosial